Hindfoot Endoscopic Treatments for the Pathologies of the Flexor Hallucis Longus and Achilles Tendons - Chayanin Angthong; Cholawish Chanlalit; Henry R Handoyo (My University, 2022)
Treatments Achilles Tendon RuptureConservative treatments could be considered for incomplete and complete ruptures; however, this method yields a high rate of rerupture in cases of complete rupture. 6Operative treatments have been proposed for open, mini-open, and endoscopic techniques.Although the open technique causes a higher risk of soft-tissue complications than other treatments, there is no consensus to date on the best technique for tendon repair.This article focuses on endoscopic techniques to treat this injury, especially chronic rupture.Since endoscopic treatment has a lower need for a large incision, there is no need to wait for the reduction of swelling before the surgery in case of acute rupture.This treatment should be performed within a few days following the injury since a delay could complicate the attachment of the proximal and distal segments of the tendon.Although this procedure generates good results, sural nerve injury is a potential complication. 7,8he authors of the present study preferred to focus on the endoscopic treatment of chronic rupture that could be safely treated
Keywords: Tendon Structure and Treatment